VD_FINDINFO Jug / 2021 / 86 vom 29. Oktober 2020 - VD Tribunal cantonal (2020)
CONSTATATION DES FAITS, FIXATION DE LA PEINE, SURSIS PARTIEL À L'EXÉCUTION DE LA PEINE, EXPULSIONDROIT PÉNAL, COMPLICITÉ, VOLDROIT PÉNAL | 25 CP, 286 CP, 43 al. 1 CP, 46 al. 1 CP, 47 CP, 49 al. 1 CP, 66a CP, 10 CPP (CH), 398 al. 3 let. b CPP (CH)